Age Peculiarities of Professional Self-Realization of Personality (by the Example of the Experts in Marketing from the People's Republic of China) - - Chzhan Ten (Peoples' Friendship University of Russia (RUDN University), 2013)
The results of the empirical research carried out on the sample of the experts in marketing from China are discussed in the article. The age aspects of the professional self-realization of the respondents are analyzed. The research was carried out within the framework of the polysystem concept of the personality self-realization.